The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-27359-4
|View full text |Cite
|
Sign up to set email alerts
|

NMR-based Metabolomic Techniques Identify the Toxicity of Emodin in HepG2 Cells

Abstract: Emodin is a natural anthraquinone derivative that is present in various herbal preparations. The pharmacological effects of emodin include anticancer, hepatoprotective, anti-inflammatory, antioxidant and even antimicrobial activities. However, emodin also has been reported to induce hepatotoxicity, nephrotoxicity, genotoxicity and reproductive toxicity. The mechanism of emodin’s adverse effects is complicated and currently not well understood. This study aimed to establish a cell metabonomic method to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…As DMA is toxic to the cells, it might be excreted into the cell culture media. KKU-100 cells showed a decrease in the level of glutamine as in a similar report on emodin treatment for HepG2 cells [ 41 ]. The phosphorylation of ribose from inosine generates hypoxanthine by purine nucleoside phosphorylase (PNP) in a salvage pathway.…”
Section: Discussionsupporting
confidence: 72%
“…As DMA is toxic to the cells, it might be excreted into the cell culture media. KKU-100 cells showed a decrease in the level of glutamine as in a similar report on emodin treatment for HepG2 cells [ 41 ]. The phosphorylation of ribose from inosine generates hypoxanthine by purine nucleoside phosphorylase (PNP) in a salvage pathway.…”
Section: Discussionsupporting
confidence: 72%
“…The different doses of emodin (25–400 μM) were applied to ejaculated human sperm, showed that sperm functions were inhibited by reducing sperm [Ca(2+)]i and prohibiting tyrosine phosphorylation in vitro ( Luo et al., 2015 ). In addition, it was found that 24 h emodin (100 μM) interrupted several metabolites and biological processes including amino acid metabolism, purine metabolism, and Krebs cycle disruption ( Chen et al., 2018 ). Since the ROS scavenging agent NAC can counteract the toxic effect of emodin, the increase in mitochondrial reactive oxygen production was also considered as an aspect of emodin toxicity ( Kolitsida and Abeliovich, 2017 ).…”
Section: Toxicitymentioning
confidence: 99%
“…Metabolomics offers a trustable and effective tool to investigate the behaviour of biological systems by analysing their metabolic fingerprint 10 . Many applications have been described so far in the characterisation of the metabolic profile of plants 11 , 12 , as well as in the assessment of changes of the metabolic signature after a selected treatment, such as plant-derived medicines and conventional drugs 13 , or plant-derived metabolites 14 . Here, we aimed at further characterising the effect of Crithmum maritimum in HCC cells by using a metabolomic approach.…”
Section: Introductionmentioning
confidence: 99%